Bioweathering in monogenetic volcanoes: the case of Xitle in Mexico City - Maria del Pilar Ortega-Larrocea; María Fernanda Martínez Báez-Téllez (Geofísica Internacional)
This contribution describes biological weathering features produced by microbial communities growing on rock surfaces denominated biological rock crusts. We provide arguments related to the importance of recognizing rocks as an ecological niche and a review of main recognized bio-weathering processes in basaltic bedrock. We particularly address the features found in the lava flow of the monogenetic volcano Xitle, which is located in the volcanic field of the Sierra del Chichinautzin in the south of Mexico City. We found that the diversity and distribution of organisms within the rock crusts varies depending on the superficial texture and porosity of the lavas. Mosses have a preference for vesicles and crevices, while lichens can establish in smoother and more exposed areas. The predominant biological weathering features we have found associated with these crusts are incrustation, penetration, vesicle infilling, endolithic colonization, fractures, and particle entrapment. It is worth noting that bioweathering features are related to specific biological groups: lichens exert all of the features found, while mosses are mostly associated with particle entrapment and vesicle infilling, and biofilms are related to penetration and endolithic colonization. Therefore, this article discusses the importance of geoheritage conservation in relation to the biodiversity these lavas harbor.